(untitled) (Revista Tecnológica, 2019)
The palm tree Butia yatay (Mart.) Becc. occurs naturally in the municipality of Giruá, of the state of Rio Grande do Sul. Currently, it is in population decline, due to extensive agriculture and livestock activities that are expanding. In response to ecological pressures, many secondary compounds are synthesized by plants which perform several ecological functions. The main aim of this study was to characterize the foliar secondary metabolites of Butia yatay. Ten samples of the leaves of the species were collected, five of which were selected in the urban zone and five in the countryside of the municipality of Giruá. With foliar extracts, the qualitative phytochemical characterization of the secondary metabolites was carried out by means of specific chromatic tests. It was verified the presence of four classes of secondary metabolites: coumarins, flavonoids, saponins, and tannins. These compounds are assigned important functions in plants against biotic and abiotic factors. Moreover, they are of great interest to human health, especially from a pharmacological point of view due to the description of their biological effects.